Iron-Catalyzed Acceptorless Dehydrogenative Coupling of Alcohols With Aromatic Diamines: Selective Synthesis of 1,2-Disubstituted Benzimidazoles - Putta, Ramachandra Reddy; Chun, Simin; Lee, Seok Beom; Oh, Dong-Chan; Hong, Suckchang (Frontiers in Chemistry, 2020)
Benzimidazoles are important N-heteroaromatic compounds with various biological activities and pharmacological applications. Herein, we present the first iron-catalyzed selective synthesis of 1,2-disubstituted benzimidazoles via acceptorless dehydrogenative coupling of primary alcohols with aromatic diamines. The tricarbonyl (η4-cyclopentadienone) iron complex catalyzed dehydrogenative cyclization, releasing water and hydrogen gas as by-products. The earth abundance and low toxicity of iron metal enable the provision of an eco-friendly and efficient catalytic method for the synthesis of benzimidazoles.